Captain underpants and the invasion of the incredibly naughty cafeteria ladies from outer space (and the subsequent assault of the equally evil lunchroom zombie nerds) (New York: Scholastic, 2000)
Harold and George's crazy reaction is back-in adventure that's wedgier than ever! He defeated the diabolic Dr. Nappy... He terminated he terrible talking toilets... But is Captain Underpants ready to take on three massive tentacled space aliens (in disguise)?